Food Stress in Adelaide: The Relationship between Low Income and the Affordability of Healthy Food. (29th January 2013) - Ward, Paul R.; Verity, Fiona; Carter, Patricia; Tsourtos, George; Coveney, John; Wong, Kwan Chui
Abstract : Healthy food is becoming increasingly expensive, and families on low incomes face a difficult financial struggle to afford healthy food. When food costs are considered, families on low incomes often face circumstances of poverty. Housing, utilities, health care, and transport are somewhat fixed in cost; however food is more flexible in cost and therefore is often compromised with less healthy, cheaper food, presenting an opportunity for families on low incomes to cut costs. Using a "Healthy Food Basket" methodology, this study costed a week's supply of healthy food for a range of family types. It found that low-income families would have to spend approximately 30% of household income on eating healthily, whereas high-income households needed to spend about 10%. The differential is explained by the cost of the food basket relative to household income (i.e., affordability). It is argued that families that spend more than 30% of household income on food could be experiencing "food stress." Moreover the high cost of healthy foods leaves low-income households vulnerable to diet-related health problems because they often have to rely on cheaper foods which are high in fat, sugar, and salt.